Colonial primary education in Kabylia: Alfred Rambaud’s perspective - Hocine , Mezhoura l’hadj Salhi (The Algerian Historical Journal, 2026)
Rambaud provides an overview of colonial primary education policy in Kabylia, highlighting assimilation and evangelization strategies, as well as ethnic division to facilitate control. Missionaries were central to the evangelization and francization of the Kabyles. After 1870, republican education, introduced by the 1883 law making elementary school compulsory, also sought to erode the cultural and religious foundations of the Kabyles. Rambaud, who was close to Jules Ferry, defended this schooling policy while criticizing its limitations, emphasizing the intelligence of Kabyle pupils but lamenting the lack of resources and insufficient commitment of the colonial authorities. Kabyle school enrolment remained low, reflecting the tensions between assimilation and local traditions, as well as the uneven priorities of colonization.